Entropy of a Probability Distribution of Transactions/Uses: A Measure of Concentration of Transactions/Uses over Documents - Ravichandra Rao, I. K. (Journal of Information and Knowledge, 1979)
Discusses entropy as a measure of concentration of transactions/uses over documents. It is found that higher the entropy, the lower the degree of concentration of transactions/uses over documents and vice-versa.